Advancing wheat breeding in Ethiopia: Challenges and opportunities in breeding for nutrient use efficiency: A review - Tesfaye Geleta Aga (Agrosystems, Geosciences & Environment)
Abstract Wheat plays a critical role in Ethiopia's food security, nutrition, and economic development. Despite increased production and expansion into diverse agro‐ecological zones, productivity remains constrained by soil nutrient depletion, inefficient fertilizer use, and low adoption of best agronomic practices. This review explores the status, challenges, and opportunities in wheat breeding for nutrient use efficiency (NUE) in Ethiopia. Improving NUE is essential for sustainable agriculture, reducing production costs, and minimizing environmental impact. Implementing best management practices and harnessing genetic diversity are crucial for enhancing NUE. This review highlights the need to develop cultivars with improved root systems and superior nutrient uptake and utilization. Although Ethiopian research systems have released high‐yielding, stress‐tolerant, and micronutrient‐enriched wheat varieties, targeted breeding for NUE is still in its early stages. Notable progress includes breeding for acid and salt tolerance, and recent identification of durum wheat genotypes with high nitrogen uptake and utilization efficiency provides new avenues for improvement. However, this progress is impeded by challenges such as limited molecular techniques, inadequate infrastructure, and a narrow genetics base, particularly for bread wheat. Opportunities lie in the high genetic diversity, particularly in durum wheat, access to global germplasm sources, diverse agro‐ecological zones, and collaboration with international research organizations. Addressing these challenges and leveraging opportunities can improve wheat breeding for nutrient efficiency, contributing to food security and sustainable wheat production in Ethiopia under climate variability.